Incubation period of coronavirus disease 2019: new implications for intervention and control. - Huang, Shunxiang; Li, Jing; Dai, Chengguqiu; Tie, Zihan; Xu, Jiazhao; Xiong, Xiang; Hao, Xingjie; Wang, Zhongyi; Lu, Chan (International Journal of Environmental Health Research, 2022)
The COVID-19 pandemic has been causing serious disasters to mankind. The incubation period is a key parameter for epidemic control and also an important basis for epidemic prediction, but its distribution law remains unclear. This paper analyzed the epidemiological information of 787 confirmed non-Wuhan resident cases, and systematically studied the characteristics of the incubation period of COVID-19 based on the interval-censored data estimation method. The results show that the incubation period of COVID-19 approximately conforms to the Gamma distribution with a mean value of 7.8 (95%CI:7.4–8.5) days and a median value of 7.0 (95%CI:6.7–7.3) days. The incubation period was positively correlated with age and negatively correlated with disease severity. Female cases presented a slightly higher incubation period than that of males. The proportion of infected persons who developed symptoms within 14 days was 91.6%. These results are of great significance to the prevention and control of the COVID-19 pandemic.